IMPLEMENTASI KEBIJAKAN PENERIMAAN MAHASISWA - ', Hamidi (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Admissions Policy Implementation. This study aims to determine the application of new admissions policies at the University of Riau through PBUD. The method used is descriptive qualitative method. The informants are officials in academia at the University of Riau, school principals, teachers, students, parents of students and school students. Data collection technique were interview, observation and documentation. Data analysis started from the presentation of data, data reduction and conclusion. The results showed that PBUD has provided a great opportunity for outstanding students in SMA/MA/SMK to continue their education to state universities. But with the enactment of Ministerial Regulation No. 34 Year 2010 on Pattern Admissions Graduate Program on Higher Education organized by the Government has been far opportunities for local people to continue their education to a higher level.